2021
DOI: 10.1177/08862605211015220
|View full text |Cite
|
Sign up to set email alerts
|

Male Victims at a Dutch Sexual Assault Center: A Comparison to Female Victims inCharacteristics and Service Use

Abstract: Recently, there has been an increase in referrals of male victims of sexual assault to interdisciplinary sexual assault centers (SACs). Still, there is limited research on the characteristics of men who refer or are referred to SACs and the services they need. To facilitate the medical, forensic, and psychological treatment in SACs, a better understanding of male victims is indispensable. The first aim of the study was to analyze the victim and assault characteristics of male victims at a Dutch SAC, and to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
3
1
1
Order By: Relevance
“…The differences in proportions in these results suggest that fathers and stepfathers are more frequently identified as aggressors against female victims, while uncles and cousins are more often implicated in male victims. Although previous literature does not indicate a specific relationship between the victim’s gender and the type of relationship with the perpetrator, 19 , 20 reports with a relatively small sample size contrast their findings with the results presented in this study, particularly in terms of highlighting the different family members who perpetrate violence against female and male victims. It is noteworthy that the prevalence of cousin as the perpetrator is higher in male victims, 21 similar to the findings of this study.…”
Section: Discussioncontrasting
confidence: 99%
“…The differences in proportions in these results suggest that fathers and stepfathers are more frequently identified as aggressors against female victims, while uncles and cousins are more often implicated in male victims. Although previous literature does not indicate a specific relationship between the victim’s gender and the type of relationship with the perpetrator, 19 , 20 reports with a relatively small sample size contrast their findings with the results presented in this study, particularly in terms of highlighting the different family members who perpetrate violence against female and male victims. It is noteworthy that the prevalence of cousin as the perpetrator is higher in male victims, 21 similar to the findings of this study.…”
Section: Discussioncontrasting
confidence: 99%
“…22,23 However, a study conducted at a Sexual Assault Centre in the Netherlands found that there was no significant difference in victim or assault characteristics between males and females, although, unlike our study, this paper contained a small sample size of males in comparison to females. 24 Future research could consider vulnerability factors to improve our understanding of client populations most at risk of assault.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding pre-assault factors, our study included only female victims. Although the Dutch Sexual Assault Centres have noticed an increase in male referrals over the years (Covers, Teeuwen et al, 2021 ), male victims are still underrepresented. The main reason for underrepresentation is that male victims are less likely to disclose and seek help (De Graaf & Wijsen, 2017 ).…”
Section: Discussionmentioning
confidence: 99%